E-038 Stenting for Pseudotumor: The Conduit Technique. (14th July 2013) - Chaudry, I; Spiotta, A; Hawk, H; Miranpuri, A; Turner, R; Turk, A
Abstract : Introduction: Carefully selected pseudotumor cerebri patients with dural sinus stenosis and pressure gradients can be considered for sinus stenting. The tortuous sigmoid sinus-jugular bulb junction and transverse-sigmoid sinus stenosis can contribute to the complexity of stent delivery. Materials and Results: Distal access guide catheters as 6Fr 070 Neuron guide catheters and 6Fr 088 Neuron Max sheaths (Penumbra, Inc., Alameda, CA), 6Fr Shuttle sheaths (Cook Medical, Inc., Bloomington, IN), 6Fr Chaperon guide catheters (Microvention-Terumo, Irvine, CA), over a diagnostic insert catheter can provide distal support during delivery of Cordis Precise stents (Cordis Corporation, Bridgewater, NJ). We report nineteen cases where the guide catheter was able to achieve access beyond the jugular bulb and in all cases the stent was successfully deployed across the target lesion. No guide catheter or stent complications were encountered in our series. Conclusion: We outline our "conduit" approach in sinus stenting using distal access guide catheters which allows for superior navigability and trackability of the guide catheters across the tortuous and stenotic sinus system, and successful deployment of the stent. Disclosures: I. Chaudry: 2; C; Penumbra, Microvention. A. Spiotta: None. H. Hawk: None. A. Miranpuri: None. R. Turner: 2; C; Microvention, Penumbra. A. Turk: 2; C; Penumbra, Microvention.